Kajian Nilai dan Konsep Pengobatan Tradisional Pada Lontar Usada Yeh - Asthadi Mahendra Bhandesa; Nadya Treesna Wulansari; I Putu Agus Endra Susanta (Jurnal Penelitian Agama Hindu, 2022)
Usada yeh is essentially a usada lontar that contains the types of diseases, methods of treatment using water and mantras, and various other upakara facilities. In Usada yeh, the composition and order of the dasaksara were known as the primary basis for using the usada treatment. The purpose of this study was to analyze the value and concept of traditional medicine in usada yeh lontar. This study was employed descriptive qualitatively using an ethnomedicine approach. The data were analyzed through content analysis of lontar usada yeh and in-depth interviews with a pangusadha and academics in Hinduism. The finding indicated that: The values contained was the value of theological education in the form of the teachings of divinity and worship of Tri Purusa (Parama Shiva, Sada Shiva, and Shiva), and the value of health education, such as knowledge about various diseases, treatment methods, knowledge of usada mantram and means based on Shivaistic concepts through tantric teachings. The concept of usada yeh traditional medicine was based on an understanding of the composition and sequence of dasaaksara, in the form of treatment for all kinds of diseases using several means, namely water, mantram, drops, herbal medicine, spray, powder, usug, sesayut, caru, daksina, and other rituals. Moreover, usada yeh could be implemented by combining any type of wood tree. In conclusion, the values and concepts of traditional medicine in lontar usada yeh are centered on water, mantram and ingredients made from natural ingredients and other rituals.